Shakespeare’s Time: Culture, Society and Economy from a Literary Perspective (Cultura Económica, 2018)
Within the vast work of William Shakespeare, two texts stand out for the possibilities presented in terms of socioeconomic aspects relevant to the human being: The Merchant of Venice and Timon of Athens. Based on a commentary on the context of production, we attempt to propose an interpretation that, based on contemporary historical and critical sources, accounts for that of the author’s in regard to this dimension.
Keywords: Shakespeare; theatre; social aspects; economic aspects; historical interest